Analisis dan Implikasi terhadap Penegakan Hukum di Indonesia - Reynold Simanjuntak; Apriska Sibarani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The constitutional procedural law in Indonesia plays a crucial role in upholding constitutional supremacy, with the Constitutional Court (MK) serving as the guardian that reviews laws and resolves constitutional disputes. This article discusses the procedural law in MK, the challenges it faces, and its impact on law enforcement and justice in Indonesia. The enforcement of justice in Indonesia remains far from ideal, reflected in the chaotic legal system, structure, and culture. This study examines the Kanjuruhan Tragedy to provide an insight into the practice of law enforcement. The findings show that the state is legally responsible for the incident due to its failure to protect and fulfill the human rights of the victims. However, law enforcement in Indonesia remains discriminatory, sharp against the lower classes, yet blunt against the elites. It is hoped that law enforcement officers and the government will be more attentive and aware of the importance of fair justice enforcement, ensuring that all citizens receive legal certainty, order, and protection based on truth and justice.